COMMUNITY EMPOWERMENT THROUGH WASTE REDUCTION DOMESTIC BASED ON RECYCLED PRODUCTS IN MARGATANI VILLAGE, KRAMATWATU DISTRICT, SERANG REGENCY - Arta Rusidarma Putra; Basuki Rakhim Setya Permana; Bambang Setyo Panulisan (Yayasan Education and Social Center, 2022)
This community partnership program aims to invite and empower the community to play an active role in increasing environmental awareness by providing education, assistance, and evaluation to process household waste and used cooking oil into various handicraft products. This activity has economic value with implementing a Digital Waste Bank and evaluation and development related to the marketing strategy of handicraft products. This activity is based on the problems related to the lack of public awareness in protecting the environment, as seen from the many points of garbage that should not be seen piling up in the surrounding environment. The lack of public knowledge about waste management and converting waste into goods of economic value by utilizing the waste itself. The priorities agreed to be resolved to relate to 1) Increasing environmental awareness, 2) How to manage household waste properly, 3) How to process plastic sachets into handicrafts with economic value, 4) How to manage used cooking oil into products. The solutions provided are socializing environmental awareness and training (coaching and mentoring) on household waste management in collaboration with digital waste banks integrated with e-wallets such as Dana, OVO, Gopay, Shopeepay, and others. Training on plastic processing of food, beverage, and plastic detergent or dishwasher products into crafts and used cooking oil into soap can be sold and generate economic value